Data clustering study of information and communication technology abilities among adolescents and adults in indonesia - Muchamad Sobri Sungkar; Warkianto Widjaja; Edy Winarno; Hamid Wijaya; Firman Aziz (Institute of Computer Science (IOCS), 2023)
Information and communication technology (ICT) has become an integral part of daily existence in the digital age. Internet penetration, smartphone usage, and the adoption of technology-based applications have all accelerated the growth of ICT usage in Indonesia. Nonetheless, not everyone has the same level of proficiency with ICT. In order to comprehend the characteristics of ICT users in Indonesia, the research seeks to classify ICT proficiency among adolescents and adults in Indonesia. This study classifies ICT proficiency data among adolescents and adults in Indonesia using data mining techniques, specifically the K-Means clustering algorithm. The classification of ICT proficiency data among adolescents and adults in Indonesia based on predetermined characteristics is the outcome of this study. The results indicate that provinces close to the capital city center tend to have a high proportion of 15- to 24-year-olds with ICT skills. The region of Papua that is farthest from the capital city has the lowest percentage of ICT proficiency. Rural areas typically possess fewer ICT skills than urban ones.